Accelerating Permit Issuances for Renewable Energy Projects - Žilinskienė, Leda (Teisė, 2025)
One of the most important measures in terms of promoting the development of renewable energy is the simplification of permit-issuing procedures for renewable energy projects. A number of recent legal acts in this area have been adopted at the EU level, including Directive 2023/2413, also known as RED III. Amendments contained within this have been criticised for lowering environmental protection and impacting assessment standards. A less frequently discussed but yet equally important aspect is the relationship between national administrative law and EU rules on permitting renewable energy projects. The preparation of this article was prompted by the fact that the simplification of permit procedures for renewable energy projects has a significant impact on the member state administrative systems and governance structures. One of the article’s main objectives is to examine, from the perspective of administrative law, EU and Lithuanian legal frameworks where these relate to procedures for granting permits for renewable energy projects. The research is conducted through an assessment of the general legal regulation of permit issuance in Lithuania, and the task io linking this aspect with innovations which have been introduced by the EU in terms of permit procedures for renewable energy projects. Both the Lithuanian legal system and its doctrine are facing several challenges: it is necessary to systematise and clearly regulate general provisions for permit issuance while, at the same time, in specific sectors such as the issuance of permits for renewable energy projects, new EU permitting provisions are being introduced which have previously been unknown to national law.
Keywords: renewable energy; permit-granting procedure; administrative law; Directive 2023/2413; RED III